في تعليم مهارة الكلام (The Flipped Classroom) تطبيق الفصل المقلوب - Fitriyah, Radiatul; Machmudah, Umi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
In today's era, teachers must be able to teach through the use of technology because today's education is different from the past, nowadays many students are familiar with technology. And by implementing flipped classroom in teaching speaking skills, this is one solution to increase the interaction between teachers and students using education through technology. The purpose of this study is to describe how to apply reverse classroom instruction and then to find out the advantages and disadvantages of teaching speaking skills. The researcher uses qualitative research and the type of research is a case study. The data and sources are primary secondary data, teachers and students. And secondary data documents, official and preparatory teaching process, and the pillars. Then the method of all data is the method of observation, interviews, documents and open questionnaires, and qualitative and descriptive analysis are used in data analysis. The educational process of MTs Hasanah Bakanbaru from a face-to-face education system in offline classes to home-based education via the internet using Zoom, Googlemate and WhatsApp. And on the application of teaching speaking skills using an integrated type of education, including reverse classes. The advantage of reverse classroom education is more relaxed and free time anytime and anywhere to collect assignments, and with this model they become more free to read additional topics from google etc. And the disadvantages include short study time, internet, and many students who do not understand the material. The results of this study can be used as a reference in the application of mixed Arabic education and are considered to reduce failure.